2002
DOI: 10.1152/jn.00423.2001
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Enhancement of Glutamate-Mediated Responses by Serotonin and Forskolin in Adult Mouse Spinal Dorsal Horn Neurons

Abstract: Wang, Guo-Du and Min Zhuo. Synergistic enhancement of glutamate-mediated responses by serotonin and forskolin in adult mouse spinal dorsal horn neurons. J Neurophysiol 87: 732-739, 2002; 10.1152/jn.00423.2001. Glutamate is the major excitatory amino acid neurotransmitter in the CNS, including the neocortex, hippocampus, and spinal cord. Normal synaptic transmission is mainly mediated by glutamate AMPA and/or kainate receptors. Glutamate N-methyl-Daspartate (NMDA) receptors are normally inactive and only activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 70 publications
2
40
0
1
Order By: Relevance
“…Similar synergism has been seen before be-tween forskolin and the stimulatory effects of isoproterenol [17], prostaglandin E 2 [18], serotonin [19] and the cannabinoid agonist HU210 [7]. This synergistic effect may imply a real cooperation between the various cellular components, or may simply result from experimental limitation of background noise, and the requirement to augment the signal by forskolin, so that the effect of DALN on cAMP formation can be discerned.…”
Section: Discussionsupporting
confidence: 65%
“…Similar synergism has been seen before be-tween forskolin and the stimulatory effects of isoproterenol [17], prostaglandin E 2 [18], serotonin [19] and the cannabinoid agonist HU210 [7]. This synergistic effect may imply a real cooperation between the various cellular components, or may simply result from experimental limitation of background noise, and the requirement to augment the signal by forskolin, so that the effect of DALN on cAMP formation can be discerned.…”
Section: Discussionsupporting
confidence: 65%
“…In addition to cortical region, AC1 is also likely involved in spinal cord plasticity. In previous studies, we have demonstrated that genetic deletion of AC1 inhibits spinal cord LTP induced by pairing training protocol and synaptic facilitation induced by coapplication of forskolin and serotonin (Wang and Zhuo, 2002;Wei et al, 2006). Considering the increasing evidence of spinal LTP and descending facilitation in chronic pain, it is conceivable that spinal AC1 mechanisms may also contribute to allodynia.…”
Section: Calcium-stimulated Ac1 In Synaptic Plasticity and Painmentioning
confidence: 99%
“…''ON'' cells facilitate pain perception, whereas ''OFF'' cells take part in descending inhibition of pain (Fields, 2006). In the dorsal horn, 5-HT 1A receptors reduced pronociceptive transmission by reducing responsiveness of neurons to glutamate (Lopez-Garcia, 1998), whereas 5-HT 2 receptors activated ''silent'' glutaminergic neurons (Li and Zhuo, 1998;Wang and Zhuo, 2002), probably through recruitment of postsynaptic AMPA receptors (Li et al, 1999). This neuronal activation is believed to contribute to the expanded field of mechanical hyperalgesia that is characteristic of central amplification.…”
Section: Mechanisms Of Central Amplification Supported Bymentioning
confidence: 99%